2022
DOI: 10.1021/acsestwater.2c00467
|View full text |Cite
|
Sign up to set email alerts
|

Snapshot ARG Removal Rates across Wastewater Treatment Plants Are Not Representative Due to Diurnal Variations

Abstract: To evaluate the threat of the environmental dissemination of antibiotic resistance associated with wastewater treatment plants (WWTPs), the removal efficiency of antibiotic resistance genes (ARGs) during wastewater treatment needs to be assessed. The sample collection strategy is one factor that is often overlooked in study design and most studies on ARGs in wastewater perform grab sampling. Here, we hypothesized that wastewater sampling (i.e., grab and composite sampling) influences the observed ARG concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
(105 reference statements)
0
0
0
Order By: Relevance
“…The results of this study indicate that sampling only at the pond banks may result in an overestimation of the average ARB concentrations, while sampling only at the interior may result in an underestimation. While this study did not delve into the temporal dynamics of ARB in the studied irrigation ponds, recent research has shown that the time of day in which samples are collected may also be a significant factor governing ARB/ARG concentrations in surface waters (Lou et al, 2022;Nguyen et al, 2022) which should be accounted for in design of monitoring programs. Additionally, future work should investigate how environmental compartments for AMR in aquatic systems, such as sediments or biofilms, impact the measured concentrations in the water column.…”
Section: Discussionmentioning
confidence: 89%
“…The results of this study indicate that sampling only at the pond banks may result in an overestimation of the average ARB concentrations, while sampling only at the interior may result in an underestimation. While this study did not delve into the temporal dynamics of ARB in the studied irrigation ponds, recent research has shown that the time of day in which samples are collected may also be a significant factor governing ARB/ARG concentrations in surface waters (Lou et al, 2022;Nguyen et al, 2022) which should be accounted for in design of monitoring programs. Additionally, future work should investigate how environmental compartments for AMR in aquatic systems, such as sediments or biofilms, impact the measured concentrations in the water column.…”
Section: Discussionmentioning
confidence: 89%
“…Variable persistence of microbes and their DNA can be influenced by factors such as treatment strategy utilized ( 50 ), air temperature, and elevation ( 51 ). Within a facility, the time of the day the sample is collected ( 52 ), flow rate ( 53 ), and seasonal effects ( 54 ) can all influence microbial concentrations. Post-secondary treatment stages in AWT facilities sampled here include anoxic basins and oxidation ditches, dual media deep-bed denitrification filters, activated sludge treatment in an anoxic/aerobic configuration, and a five-stage Bardenpho activated sludge process, each of which could feasibly contribute to the reduction of DNA in recycled water.…”
Section: Discussionmentioning
confidence: 99%